2004
DOI: 10.1111/j.1742-1241.2004.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of angiotensin-converting enzyme gene polymorphism in Turkish hypertensive patients

Abstract: Hypertension is a multifactorial disease, in which genetic factors play an important role. This study was carried out to determine angiotensin-converting enzyme levels and angiotensin-converting enzyme gene polymorphism in Turkish hypertensive patients, and to establish whether there is an association of angiotensin-converting enzyme gene polymorphism with clinical and echocardiographic parameters. We have investigated the association among the allelic distribution of the insertion/deletion (I/D) polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
1
24
0
4
Order By: Relevance
“…The DNA of each individual was isolated from the blood samples using the salt method as previously described (Gunes et al 2004). As described in the same study, amplification of the DNA samples was performed using the sense oligonucleotide primer 5 0 CTG CAG ACC ACT CCC ATC CTT TCT 3 0 and the antisense oligonucleotide primer 5 0 GAT GTG GCC ATC ACA TTC GTC AGA T 3 0 designed to detect ACE I/D polymorphism (Gunes et al 2004).…”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA of each individual was isolated from the blood samples using the salt method as previously described (Gunes et al 2004). As described in the same study, amplification of the DNA samples was performed using the sense oligonucleotide primer 5 0 CTG CAG ACC ACT CCC ATC CTT TCT 3 0 and the antisense oligonucleotide primer 5 0 GAT GTG GCC ATC ACA TTC GTC AGA T 3 0 designed to detect ACE I/D polymorphism (Gunes et al 2004).…”
Section: Genotypingmentioning
confidence: 99%
“…The DNA of each individual was isolated from the blood samples using the salt method as previously described (Gunes et al 2004). As described in the same study, amplification of the DNA samples was performed using the sense oligonucleotide primer 5 0 CTG CAG ACC ACT CCC ATC CTT TCT 3 0 and the antisense oligonucleotide primer 5 0 GAT GTG GCC ATC ACA TTC GTC AGA T 3 0 designed to detect ACE I/D polymorphism (Gunes et al 2004). One hundred nanograms of genomic DNA samples was amplified by 30 cycles of denaturation at 92°C for 40 s, annealing at 56°C for 40 s and extension at 72°C for 40 s, using a 50 ll of PCR mixture containing 10 pmol of each primer, 19 PCR buffer (Vivantis Technologies, Selangor, Malaysia) with magnesium chloride, 2.5 mM dNTPs, and 1.25 U of thermostable Taq polymerase (Vivantis Technologies).…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pathogenesis of hypertension is not clearly known (Gunes et al 2004;Bayramoglu et al 2012). Recently, the application of genetic approaches to this disease has begun to delineate molecular pathways underlying blood pressure variation, defining disease pathogenesis and identifying targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of genetic approaches to this disease has begun to delineate molecular pathways underlying blood pressure variation, defining disease pathogenesis and identifying targets for therapeutic intervention. It is suggested that many genes have influences on the pathogenesis of hypertension (Lifton et al 2001;Gunes et al 2004;Bayramoglu et al 2012). This pathologic process is characterized by structural changes in the arterial wall caused by increased deposition of extracellular matrix (ECM) components, particularly collagen, as well as alterations in ECM architecture or cell-extracellular matrix attachments (Derosa et al 2006;Bayramoglu et al 2012).…”
Section: Introductionmentioning
confidence: 99%